Language Styles in Biography: A Descriptive Analysis of Ernle Bradford's 'The Sultan's Admiral: Barbarossa – Pirate and Empire Builder' - Zenith Nurandini Ramadhan; Engliana Engliana; Nina Dwiastuty (Makassar State University, 2022)
Abstract. This research aims to identify the language styles used in a biography book, ‘The Sultan’s Admiral.’ The identification may help us see how various language styles add to non-fiction writing and are structured in a biography book. This current research is a qualitative analysis that uses a content analysis method. The data source is available from the biography ‘The Sultan’s Admiral: Barbarossa’ written by Ernle Bradford and published in English language edition in 2008. The data comes in the form of linguistic elements such as syntax, lexis, and semantic forms of the text. The data analysis technique categorizes or determines stylish language features from the sample and the level of style related to linguistics and stylistics approaches. Lexis, syntactic and semantic level of language style is prior categories of this research. As a result, the technical terms and adjectives are used in the lexical level of style, direct quotations, and em-dashed ( – ) adjuncts in sentences as the structural level of style, idioms, and figures of speech are used in the semantic level of style. Those chosen styles appear with the writer's background to give extra values to the actual story. This research describes and classifies portions among several linguistic features used by the narrator/writer in the development of narrative in Barbarossa's legendary life, to demonstrate the benefits of the technique in incorporating linguistic aspects into the text. Along with the analysis, the current research makes recommendations for future investigations. Keywords: Language Style, Stylistics, Biography, Narratology